Terminal Decline From Within- and Between-Person Perspectives, Accounting for Incident Dementia - Piccinin, Andrea M. (Oxford University Press, 2011)
OBJECTIVE. The terminal cognitive decline hypothesis has been debated for almost 50 years. This hypothesis implies a change in rate of decline within an individual. Therefore, we examine the hypothesis from a within-person perspective using a time to death chronological structure. METHOD. Scores on a Swedish version of the Wechsler Adult Intelligence Scale Information and Block Design scores from 461 OCTO-Twin Study participants with confirmed death dates were modeled using quadratic growth curve models including both age and distance from death at study entry, sex, education, and dementia diagnosis as covariates of initial performance and of linear and quadratic change over time. RESULTS. Information scores showed statistically significant evidence of slight within-person acceleration of declines in the no dementia group. Individuals with incident dementia declined more quickly, and those who were closer to death at study baseline had a stronger acceleration. Block Design scores declined but did not show evidence of such acceleration either within or across individuals. Decline was faster in incident cases closer to death at study entry. DISCUSSION. Within-person evidence of terminal decline is not as strong as previously published between-person results. Strategies for focusing models on longitudinal aspects of available data and the extent to which lack of within-person evidence for terminal decline may stem from common data limitations are discussed.